Factor Associated with Fall in the Elderly inNabonSub-district KhammuangDistrict, Kalasin Province. : A Case Control Study - dunlakan, Chalanda; Charerntanyarak, Lertchai (NU Journal of Nursing and Health Sciences, 2019)
This research was a retrospective analytical study with matched case-control. The objective was to identify factors related to falls among elderly people in Nabon sub-district, Khammuang district, Kalasin province. The sample was composed of 202 elderly of people over 60 years old, living in Nabon sub-district, Khammuang district, Kalasin province during1 October, 2015 to 30 , September 2016. The case group were 101 elderly people with history of falls and control group were 101 elderly people with no history of falls in the same period of time. Case and control groups were matched by sex and age ( 2 years). Data were collected using interviewing questionnaire.Risk factors include personal, behavioral and environmental history. For data analysis, a multivariate analysis using multiple logistic regression to identify factors related to falls in elderly was done. The results showed that the factors significantly related to falls were characteristic of House floor (ORadj = 5.29, 95% CI : 2.06-13.61, p = 0.001), bathroom was located outside the house (ORadj = 4.08, 95% CI : 1.64-10.11, p = 0.002), the bathroom floor was wet and slippery (ORadj = 6.22, 95%, CI :1.32-29.16, p = 0.005) and the outside of the house has inadequate lighting (ORadj = 9.05, 95% CI : 1.83-44.74, p = 0.001). From the results of this study, it can be recommended that: local public health officials should provide knowledge about environmental management for the elderly and caregivers in order to prepare the appropriate environment for living of the elderly and decrease falls.